2019
DOI: 10.5812/aapm.100178
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as Adjuvant for Acute Pain Management

Abstract: Peri-operative pain management is one of the important tasks of medical staff. The problems arising afterwards not only have a pathophysiological adverse effect on patients, but also detrimentally affect the health system, treatment costs, and delay in discharge, for which pain management should be planned prior to surgery, and the resulting stress (1-3).Recent studies indicate a high incidence of persistent postoperative pain, and anesthesiologists should thus take proactive measures to control postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…2020; 10(2):e103624. cal use and good safety profile (11)(12)(13). Physiotherapy seems somewhat interesting, as much as educational programs are presented, especially for working adults (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…2020; 10(2):e103624. cal use and good safety profile (11)(12)(13). Physiotherapy seems somewhat interesting, as much as educational programs are presented, especially for working adults (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…First, chronic pain patients usually consult pain clinics when their pain problem interferes with their lives, or their pain intensity should be at least severe enough to urge them to seek treatment. Second, the available analgesics for acute pain might be more effective than chronic pain management modalities because multimodal and preventive analgesia are well indicated and administered in acute post-op pain settings ( 15 ). Consequently, acute pain management could be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that VAS changes were greater after 30 min in the ketamine group (29.0 mm) compared to the metoclopramide-diphenhydramine group (22.2 mm) (20). One of the most important advantages of ketamine is its various prescription methods (20,37). The Ketamine acts through various mechanisms, including the supraspinal mechanisms, cholinergic and monoamine effects, local anesthetic action, sigma receptor interaction, and NMDA receptor antagonism (34).…”
Section: Discussionmentioning
confidence: 99%